Molecular Characterization of Important Viruses Contributing to Bovine Respiratory Disease Complex in Türkiye - Ozbek, Remziye; Abayli, Hasan; Tonbak, Sukru; Sahna, Kezban (Univ Agriculture, Fac Veterinary Science, 2024)
Bovine respiratory disease complex (BRDC) is one of the most common cattle diseases, causing widespread effect in worldwide. That pathogens causing BRDC occur with coinfections may even lead irreversible losses. That is why, in this study, it is aimed to investigate crucial viral pathogens associated with BRDC [Bovine herpesvirus-1 (BoHV-1); bovine respiratory syncytial virus (BRSV), bovine viral diarrhoea virus (BVDV), Hobi-like pestivirus, bovine parainfluenza-3 virus (BPIV3)] in the same sample simultaneously. Aligned with the aim, 129 nasal swabs were collected from cattle with clinical symptoms of respiratory system disease in specific provinces of eastern and southeastern T & uuml;rkiye. Firstly, viral RNA and DNA were isolated from the samples. Subsequently, PCR and RT-PCR analyses were conducted using specific primers for the viral pathogens. The results illustrated 10.85 BRSV, 1.55 BVDV-1 and 3.8% BPIV-3 positivity rates. BoHV-1, Hobi-like pestivirus, and mixed infection were not detected in any of the samples. Samples that tested positive were sequenced to represent each province for molecular characterisation and phylogenetic analysis. They were determined that the BRSV strains (TR/Bngol04/BRSV, TR/Dyrbkr-17/BRSV, and TR/Elz-23/BRSV) obtained from this study are a part of subgroup III, BVDV strains (BVDV-1/TR-/Malatya-1 and BVDV1/TR/Elazig-29) belonged to subgroup BVDV 1l, and the BPIV-3 strains (BPIV3/M17/TUR and BPIV3/M19/TUR) were within genotype C. The findings of these studies can be valuable to minimise the losses attributed to BRDC by facilitating the development of diagnostic, molecular, and epidemiological approaches. These insights can also serve as a foundation for establishing targets for vaccine development, ultimately contributing to the reduction of BRDC.
Keywords: Bovine; Respiratory diseases; Viruses; RT-PCR; T & uuml;rkiye